2000
DOI: 10.1002/(sici)1521-3765(20000103)6:1<47::aid-chem47>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Towards Synthetic Adrenaline Receptors

Abstract: The macrocyclic bisphosphonate 2 forms complexes with amino alcohols, amines, and amino acid esters with high association constants in polar organic solvents. Exertion of solvophobic interactions inside the macrocyclic cavity in DMSO and methanol leads to specificity for guest molecules with hydrophobic moieties. Experimental evidence is presented for the insertion of the guest molecules' nonpolar groups into the macrocycle's hydrophobic cavity. NMR spectra of complexes with 2 in DMSO show a molecular imprint … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 31 publications
(7 citation statements)
references
References 1 publication
(1 reference statement)
1
6
0
Order By: Relevance
“…14 Chemical shift variations were examined to determine the nature of this host-guest association. 15 1 H NMR signals of ACh showed a small modification at its ammonium extremity (Dd max ª -0.06 ppm for CH 3 N + and CH 2 N + ) which is consistent with a weak cationic interaction with 1 (Table 1). Considering 1, the n-butyl group protons H a-d were shifted (Table 1, Dd max from +0.11 to +0.31 ppm respectively).…”
Section: Acetylcholine Recognition In Watersupporting
confidence: 52%
“…14 Chemical shift variations were examined to determine the nature of this host-guest association. 15 1 H NMR signals of ACh showed a small modification at its ammonium extremity (Dd max ª -0.06 ppm for CH 3 N + and CH 2 N + ) which is consistent with a weak cationic interaction with 1 (Table 1). Considering 1, the n-butyl group protons H a-d were shifted (Table 1, Dd max from +0.11 to +0.31 ppm respectively).…”
Section: Acetylcholine Recognition In Watersupporting
confidence: 52%
“…The recognition with para- xylene-bisphosphonates was shown with several examples of ammonium [540541] and guanidinium [528,542] cations by Schrader et al Similarly, the group demonstrated the recognition of the amidinium ion with the simple m -xylene bisphosphonate 159 .…”
Section: Reviewmentioning
confidence: 99%
“…Schrader has made progress towards the binding of small biologically important molecules with his bisphosphonate based receptors. [188][189][190][191][192] Those containing a xylene core with one or two pendent phosphonate moieties (Fig. 24) display significant binding to 1,2-and 1,3-amino alcohols 188,190 and amino sugars, 191 whilst receptors with a biaryl core are large enough to bind alkylguanidinium species.…”
Section: Natural Product Receptorsmentioning
confidence: 99%